The state of art of the taxonomy of the gastropods (Pulmonata) from the Paleocene of São José de Itaboraí Basin, Rio de Janeiro State - Rodrigues, Vanessa Maria da Costa; Fonseca, Vera Maria Medina da (Anuário do Instituto de Geociências, 2007)
Abstract